Preparation process of phenolic resin with high adhesive force

Through a high adhesion phenolic resin preparation process, the reaction conditions are controlled using catalysts and additives, and the problem of insufficient adhesion of traditional phenolic resins is solved, a more stable and efficient production process is achieved, and its application field is expanded.

CN119529206APending Publication Date: 2025-02-28PUYANG WEILIN TECH DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411776833.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The traditional phenolic resin preparation process has problems such as insufficient adhesion, unstable product performance, high cost and low production efficiency, which limits its application in the field of high-performance materials.

Method used

A high adhesion phenolic resin preparation process is adopted, including preparation of raw materials, pretreatment of reaction vessels, initial mixing, adjusting pH value, heating reaction, intermediate monitoring, additive introduction, termination of reaction and drying. This process ensures high adhesion and stable performance of the product by using an appropriate amount of catalyst and additives that enhance adhesion, controlling reaction conditions and parameters.

Benefits of technology

It significantly improves the adhesion of phenolic resin, optimizes product performance, and provides more reliable bonding performance in various application scenarios, reduces production costs, improves production efficiency, and broadens its application in special areas with high adhesion requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529206A_ABST
    Figure CN119529206A_ABST
Patent Text Reader

Abstract

The invention provides a preparation technology of high-adhesion phenolic resin, and relates to the technical field of phenolic resin preparation, and the preparation technology comprises the following steps: raw material preparation, reaction container pretreatment, initial mixing, pH value adjustment, heating reaction, intermediate monitoring, additive introduction, reaction termination, and drying. The method comprises the following steps: adding 80-150g of phenol and 120-220g of a 37% formaldehyde solution into a pretreated clean and dry reaction container, adjusting the pH value of a reaction system to 9.0-10.5 by using 3-10g of sodium hydroxide, potassium hydroxide, sodium carbonate, ammonia water or ammonium chloride as a catalyst, heating to 80-100 DEG C, continuing for 1-3 hours in the reaction process, cooling to 80-100 DEG C, filtering, washing, and drying to obtain the phenolic resin. The reaction degree is regularly monitored through methods such as a rotational viscometer and a spectrophotometric method, the monitoring interval is 20-40 minutes, and the adhesive force of the phenolic resin is remarkably improved, so that the phenolic resin can provide more reliable adhesive property in various application scenes, for example, the phenolic resin can be better attached to the surface of a base material in a coating, and the durability of a coating is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of phenolic resin preparation, and more specifically, particularly relates to a preparation process of a high-adhesion phenolic resin. Background Art

[0002] In the current material field, phenolic resin is widely used due to its good performance. However, the traditional phenolic resin preparation process has some limitations, such as insufficient adhesion, which leads to poor performance in some applications with high bonding performance requirements. At the same time, the traditional process may have problems such as unstable product performance, high cost, and low production efficiency, which limits its application and development in a wider range of fields. With the advancement of science and technology and the continuous improvement of material performance requirements in various industries, there is an urgent need for an advanced process that can prepare high-adhesion phenolic resin to meet the market demand for high-performance phenolic resin. Summary of the invention

[0003] In order to solve the above technical problems, the present invention provides a preparation process of a high-adhesion phenolic resin to solve the above problems.

[0004] A preparation process of a high-adhesion phenolic resin comprises the following steps: preparing raw materials, pre-treating a reaction container, initially mixing, adjusting pH value, heating reaction, intermediate monitoring, introducing additives, terminating reaction, and drying, adding 80-150 grams of phenol and 120-220 grams of a 37% formaldehyde solution into a pre-treated, clean and dried reaction container, stirring evenly, controlling the stirring speed to 100-300 rpm, and stirring for 20-40 minutes, so that the phenol and formaldehyde solutions are fully mixed.

[0005] Preferably, 3-10 g of sodium hydroxide, potassium hydroxide, sodium carbonate, ammonia or ammonium chloride is used as a catalyst to adjust the pH value of the reaction system to the range of 9.0-10.5. During the reaction process of heating to 80-100° C., the reaction is continued for 1-3 hours, and the reaction degree is regularly monitored by a rotational viscometer, spectrophotometry, etc., with a monitoring interval of 20-40 minutes. During the 1-2.5 hour stage of the reaction, 8-15 g of silane coupling agent (KH-550, KH-792, KH-560), titanate coupling agent (NDZ-101), maleic anhydride grafted material and other adhesion enhancing additives are added, and stirring is continued for 20-40 minutes.

[0006] Preferably, when the viscosity reaches a predetermined value and the residual formaldehyde content is less than 1%, or when infrared spectroscopy analysis shows that the functional group conversion reaches the expected level, or when the thermal stability test meets the requirements, the reaction is terminated by natural cooling, adding a terminator, rapidly cooling, or passing cold air, and the reaction product is filtered and washed 2-3 times with deionized water, ethanol, acetone, distilled water, or toluene to remove impurities, and the treated product is dried in a vacuum oven at a temperature of 60-85° C. for 3-6 hours to obtain a high-adhesion phenolic resin.

[0007] Preferably, the reaction temperature is controlled within the range of 80°C to 100°C, the reaction time is 1 hour to 3 hours, the order and speed of adding each raw material follow specific specifications, the amount of phenol is 80 g to 150 g, the amount of 37% formaldehyde solution is 120 g to 220 g, the amount of catalyst is 3 g to 10 g, and the amount of additive is 8 g to 15 g. When high-adhesion phenolic resin is used in industrial production, it is necessary to be equipped with reaction equipment and monitoring systems to ensure accurate control of process parameters and safe and stable production processes. The pH value of the reaction system is controlled between 9.0 and 10.5, the purity of the raw materials is required to be not less than 98%, the cleanliness of the production environment is required to reach Class 100,000, and the operating error of each step is required to be controlled within ±5%.

[0008] Compared with the prior art, the present invention has the following beneficial effects:

[0009] 1. Significantly improve the adhesion of phenolic resin, so that it can provide more reliable bonding performance in various application scenarios, such as better adhesion to the substrate surface in coatings and enhance the durability of the coating.

[0010] 2. The optimized preparation process makes the product performance more stable, reduces the difference between batches, ensures the consistency of product quality, and provides reliable guarantee for large-scale production.

[0011] 3. Due to the enhanced adhesion, the application of phenolic resin in special fields with high requirements for adhesion, such as aerospace, automobile manufacturing, etc., has been broadened, meeting the demand for high-performance materials in these fields.

[0012] 4. Improved technology helps reduce production costs, improve production efficiency and enhance product competitiveness in the market.

[0013] 5. The prepared high-adhesion phenolic resin has better chemical corrosion resistance and heat resistance, extending the service life of the product in harsh environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 It is a topological diagram of the production process of phenolic resin of the present invention;

[0015] Figure 2It is a topological diagram of the processing of phenolic tree raw materials of the present invention;

[0016] Figure 3 It is a topological diagram of the detection process of the present invention. DETAILED DESCRIPTION

[0017] The following embodiments of the present invention are described in further detail in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.

[0018] See also Figure 1-Figure 3 The present invention provides a preparation process of a high-adhesion phenolic resin, comprising the following steps: preparing raw materials, pre-treating a reaction container, initially mixing, adjusting pH value, heating reaction, intermediate monitoring, introducing additives, terminating reaction, and drying, adding 80-150 grams of phenol and 120-220 grams of a 37% formaldehyde solution into a pre-treated, clean and dried reaction container, stirring evenly, controlling the stirring speed to 100-300 rpm, and stirring for 20-40 minutes, so that the phenol and formaldehyde solutions are fully mixed.

[0019] Use 3-10 grams of sodium hydroxide, potassium hydroxide, sodium carbonate, ammonia or ammonium chloride as a catalyst to adjust the pH value of the reaction system to the range of 9.0-10.5. During the reaction process of heating to 80-100° C., continue for 1-3 hours, and regularly monitor the degree of reaction by means of a rotational viscometer, spectrophotometry, etc., with a monitoring interval of 20-40 minutes. Add 8-15 grams of silane coupling agent (KH-550, KH-792, KH-560), titanate coupling agent (NDZ-101), maleic anhydride grafted material and other adhesion enhancing additives during the 1-2.5 hour stage of the reaction, and continue stirring for 20-40 minutes.

[0020] When the viscosity reaches a predetermined value and the residual formaldehyde content is less than 1%, or infrared spectrum analysis shows that the functional group conversion reaches the expected level, or a thermal stability test meets the requirements, the reaction is terminated by natural cooling, adding a terminator, rapidly cooling, or passing cold air, the reaction product is filtered and washed 2-3 times with deionized water, ethanol, acetone, distilled water or toluene to remove impurities, and the treated product is dried for 3-6 hours at a temperature of 60-85° C. in a vacuum oven to obtain a high-adhesion phenolic resin.

[0021] The reaction temperature is controlled within the range of 80°C to 100°C, the reaction time is 1 hour to 3 hours, the order and speed of adding each raw material follow specific specifications, the amount of phenol is 80 grams to 150 grams, the amount of 37% formaldehyde solution is 120 grams to 220 grams, the amount of catalyst is 3 grams to 10 grams, and the amount of additives is 8 grams to 15 grams. When high-adhesion phenolic resin is used in industrial production, it is necessary to be equipped with reaction equipment and monitoring systems to ensure precise control of process parameters and safe and stable production processes. The pH value of the reaction system is controlled between 9.0 and 10.5, the purity of the raw materials is required to be no less than 98%, the cleanliness of the production environment is required to reach Class 100,000, and the operating error of each step must be controlled within ±5%.

[0022] Embodiment 1:

[0023]

[0024] Raw materials: 100 g phenol, 150 g 37% formaldehyde solution, 5 g sodium hydroxide catalyst, 10 g silane coupling agent (KH-550).

[0025] step:

[0026] Reaction vessel pretreatment: The reaction vessel was rinsed with deionized water and then dried in an oven at 120°C for 2 hours.

[0027] Initial mixing: Add phenol and formaldehyde solutions into the reaction vessel and stir for 30 minutes to mix them evenly.

[0028] Adjust pH: Slowly add sodium hydroxide catalyst to adjust pH to 9.5.

[0029] Temperature reaction: The reaction system was heated to 90°C at a heating rate of 5°C / min and reacted for 2 hours.

[0030] Intermediate monitoring: Take samples every 30 minutes to measure viscosity and residual formaldehyde content.

[0031] Additive introduction: After 1.5 hours of reaction, a silane coupling agent was added and the reaction was continued for 30 minutes.

[0032] Termination of reaction: When the viscosity reaches a predetermined value and the residual formaldehyde content is lower than 1%, the reaction is terminated by naturally cooling to 50°C.

[0033] Post-treatment: The reaction product was filtered and washed with deionized water three times.

[0034] Drying: Dry in a vacuum oven at 80°C for 4 hours to obtain a high adhesion phenolic resin.

[0035] Embodiment 2:

[0036]

[0037] Raw materials: 120 g phenol, 180 g 37% formaldehyde solution, 8 g potassium hydroxide catalyst, 12 g titanate coupling agent (NDZ-101).

[0038] step:

[0039] Reaction vessel pretreatment: The reaction vessel was cleaned with ethanol and then dried in an oven at 100 °C for 3 h.

[0040] Initial mixing: Add phenol and formaldehyde solutions to the reaction vessel and stir for 40 minutes.

[0041] Adjust pH: Add potassium hydroxide catalyst and adjust pH to 10.0.

[0042] Temperature reaction: the temperature was raised to 95°C at a heating rate of 3°C / min and the reaction was carried out for 2.5 hours.

[0043] Intermediate monitoring: sampling and testing every 40 minutes.

[0044] Additive introduction: After 2 hours of reaction, titanate coupling agent was added and the reaction was continued for 30 minutes.

[0045] Termination reaction: When the predetermined reaction index is reached, the reaction is terminated by adding a terminator.

[0046] Post-treatment: filter the product and wash with ethanol twice.

[0047] Drying: Dry in a vacuum oven at 70°C for 5 hours to obtain a high adhesion phenolic resin.

[0048] Embodiment 3:

[0049]

[0050] Raw materials: 80 g phenol, 120 g 37% formaldehyde solution, 3 g sodium carbonate catalyst, 8 g aminosilane coupling agent (KH-792).

[0051] step:

[0052] Reaction vessel pretreatment: Rinse the reaction vessel with acetone and dry it in an oven at 110°C for 2.5 hours.

[0053] Initial mixing: Pour phenol and formaldehyde solutions into a reaction vessel and stir for 25 minutes.

[0054] Adjust pH: Add sodium carbonate catalyst and adjust pH to 9.0.

[0055] Temperature reaction: the temperature was raised to 85°C at a heating rate of 4°C / min and the reaction was carried out for 1.5 hours.

[0056] Intermediate monitoring: samples were taken every 25 minutes for analysis.

[0057] Additive introduction: After 1 hour of reaction, aminosilane coupling agent was added and the reaction was continued for another 25 minutes.

[0058] Termination of the reaction: The reaction was terminated by rapidly cooling the temperature to 40°C.

[0059] Post-treatment: The reaction product was filtered and washed with acetone three times.

[0060] Drying: Dry in a vacuum oven at 60°C for 6 hours to obtain a high adhesion phenolic resin.

[0061] Embodiment 4:

[0062]

[0063] Raw materials: 150 g phenol, 220 g 37% formaldehyde solution, 10 g ammonia catalyst, and 15 g maleic anhydride grafted product.

[0064] step:

[0065] Reaction vessel pretreatment: Wash the reaction vessel with distilled water and dry it in an oven at 90°C for 3.5 hours.

[0066] Initial mixing: Place phenol and formaldehyde solutions into a reaction vessel and stir for 35 minutes.

[0067] Adjust pH value: Add ammonia catalyst dropwise to adjust pH value to 10.5.

[0068] Temperature reaction: the temperature was raised to 100°C at a rate of 2°C / min and the reaction was carried out for 3 hours.

[0069] Intermediate monitoring: sampling and testing every 35 minutes.

[0070] Additive introduction: After 2.5 hours of reaction, maleic anhydride grafted product was added and the reaction was continued for 20 minutes.

[0071] Termination of reaction: Naturally cool to 60°C to terminate the reaction.

[0072] Post-treatment: Filter the reaction product and wash it twice with distilled water.

[0073] Drying: Dry in a vacuum oven at 75°C for 4.5 hours to obtain a high adhesion phenolic resin.

[0074] Embodiment 5:

[0075]

[0076] Raw materials: 90 grams of phenol, 130 grams of 37% formaldehyde solution, 4 grams of ammonium chloride catalyst, and 9 grams of epoxy silane coupling agent (KH-560).

[0077] step:

[0078] Reaction vessel pretreatment: The reaction vessel was cleaned with toluene and dried in an oven at 105°C for 2 hours.

[0079] Initial mixing: Add phenol and formaldehyde solutions to a reaction vessel and stir for 20 minutes.

[0080] Adjust pH: Add ammonium chloride catalyst and adjust pH to 9.2.

[0081] Temperature reaction: the temperature was raised to 80°C at a heating rate of 6°C / min and the reaction was carried out for 1 hour.

[0082] Intermediate monitoring: sampling and testing every 20 minutes.

[0083] Additive introduction: After 45 minutes of reaction, epoxy silane coupling agent was added and the reaction was continued for 15 minutes.

[0084] Termination of the reaction: Rapidly cool the temperature to 30°C by passing cold air to terminate the reaction.

[0085] Work-up: filter the product and wash with toluene three times.

[0086] Drying: Dry in a vacuum oven at 85°C for 3 hours to obtain a high adhesion phenolic resin.

[0087] Data analysis comparison and raw material impact analysis of the example of high adhesion phenolic resin preparation process:

[0088] 1. Data comparison of examples

[0089]

[0090] 2. Comparison results of different raw materials

[0091] 1. Phenol dosage: 100 g of phenol was used in Example 1, 120 g in Example 2, 80 g in Example 3, 150 g in Example 4, and 90 g in Example 5. As the amount of phenol increases, the active sites in the reaction system increase, which may accelerate the reaction rate, but excessive phenol may lead to incomplete reaction, leaving more unreacted phenol.

[0092] 2. Amount of formaldehyde solution: The amount of formaldehyde solution used in Example 1 is 150 grams, in Example 2 is 180 grams, in Example 3 is 120 grams, in Example 4 is 220 grams, and in Example 5 is 130 grams. Increasing the amount of formaldehyde used will increase the degree of cross-linking of the reaction, but too much formaldehyde may increase the residual amount, affecting product performance and environmental protection.

[0093] 3. Type and dosage of catalyst: Different catalysts (sodium hydroxide, potassium hydroxide, sodium carbonate, ammonia water, ammonium chloride) have different catalytic activities and alkalinity strengths. Sodium hydroxide and potassium hydroxide have strong alkalinity, which may lead to faster reaction rates; sodium carbonate and ammonium chloride have relatively weak alkalinity and milder reactions. Increasing the amount of catalyst usually speeds up the reaction, but excessive amounts may lead to more side reactions.

[0094] 4. Additive types and dosage: Additives such as silane coupling agent (KH-550), titanate coupling agent (NDZ-101), aminosilane coupling agent (KH-792), maleic anhydride grafted material, epoxy silane coupling agent (KH-560) have different molecular structures and functional groups. They play different roles in improving the adhesion of phenolic resin. Increasing the dosage of additives may further improve the adhesion, but excessive dosage may affect other properties of the resin.

[0095] 3. Effect of different raw materials on the preparation of phenolic resin

[0096] Effect of phenol

[0097] As one of the main raw materials of the reaction, the amount of phenol used directly affects the progress of the reaction and the structure of the product. When the amount of phenol used is small, it may lead to incomplete reaction, and the molecular weight of the generated phenolic resin is low and the performance is poor.

[0098] Increasing the amount of phenol will increase the active sites in the reaction system, which is beneficial to the condensation reaction with formaldehyde and generates more cross-linked structures, thereby improving the hardness, thermal stability and mechanical properties of the phenolic resin.

[0099] However, excessive phenol may cause part of the phenol to not participate in the reaction and remain in the product, affecting the purity and performance of the resin.

[0100] Effects of formaldehyde solution

[0101] The amount of formaldehyde solution used has an important influence on the crosslinking degree and performance of phenolic resin. When the amount is insufficient, the crosslinking degree is insufficient, and the strength and heat resistance of the resin may be poor.

[0102] As the amount of formaldehyde increases, the cross-linking structure increases, and the hardness, water resistance and chemical corrosion resistance of the phenolic resin will increase.

[0103] However, excessive use of formaldehyde will not only increase costs, but may also cause excessive residual formaldehyde content, which is harmful to the environment and human health, and may also cause the resin to become more brittle.

[0104] Impact of Catalysts

[0105] The type and amount of the catalyst determine the reaction rate and selectivity. Strong alkaline catalysts (such as sodium hydroxide and potassium hydroxide) can speed up the reaction, but may cause the reaction to be too violent, difficult to control, and prone to side reactions.

[0106] Weaker alkaline catalysts (such as sodium carbonate and ammonium chloride) react relatively mildly and are easier to control the reaction process, but the reaction rate may be slower.

[0107] The appropriate amount of catalyst can ensure that the reaction is completed within the appropriate time, improving production efficiency and product quality. Too little catalyst will result in a slow reaction rate and a long production cycle; too much catalyst may lead to a decrease in resin performance.

[0108] Effect of additives

[0109] Adhesion enhancing additives such as silane coupling agents, titanate coupling agents, etc. can improve the interfacial bonding strength between phenolic resin and substrate, thereby significantly improving adhesion.

[0110] Different types of additives have different functional groups and chemical structures, and interact with phenolic resins and substrates in different ways. For example, silane coupling agents can improve adhesion by forming chemical bonds with the resin and substrate, while titanate coupling agents may enhance adhesion by improving the compatibility of the interface.

[0111] The dosage of additives needs to be properly controlled. If the dosage is too small, it cannot fully play its role in enhancing adhesion; if the dosage is too large, it may affect other properties of the resin, such as flexibility and weather resistance.

[0112] In summary, in the preparation process of high adhesion phenolic resin, the types and amounts of phenol, formaldehyde solution, catalyst and additives have an important influence on the reaction process and product performance.

[0113] The characteristics of the high adhesion phenolic resin in the present invention are as follows:

[0114] Automobile braking system: High adhesion phenolic resin can be used to manufacture brake pads in automobile braking systems. Its high adhesion can ensure that the brake pad material is tightly bonded to the metal backing plate, and can still maintain stable performance under high temperature and high pressure braking conditions, providing reliable braking effects and extending the service life of the brake pads.

[0115] Electronic Circuit Boards: This phenolic resin can be used as a laminating material or insulating coating in the manufacture of electronic circuit boards. High adhesion helps ensure that the resin is firmly bonded to the circuit board's substrate and electronic components, providing good electrical insulation and heat resistance to protect the circuit from external environmental influences.

[0116] Aerospace components: used to manufacture aircraft interior structural and decorative parts, such as cabin panels, seat components, etc. Since the aerospace field has extremely high requirements for material performance, the heat resistance, corrosion resistance and high adhesion of high adhesion phenolic resin can meet these strict requirements and ensure the reliability and safety of components during flight.

[0117] Chemical pipelines: In the chemical industry, pipelines that transport various corrosive media need to have good corrosion resistance and adhesion. High-adhesion phenolic resins can be used for the inner lining coating of pipelines to prevent chemical substances from corroding the pipelines while ensuring that the coating is not easy to fall off.

[0118] Building fireproof materials: can be made into fireproof panels or fireproof coatings. Its high adhesion enables the fireproof materials to be firmly attached to the surface of the building, playing an effective role in fire prevention and heat insulation in the event of a fire, protecting the structural safety of the building.

[0119] Wind turbine blades: As a protective coating on the surface of the blades, it can resist erosion by wind, sand, rain and ultraviolet rays, and due to its high adhesion, it is not easy to peel off under the huge stress generated by the high-speed rotation of the blades.

[0120] High-end furniture surface treatment: applied to the surface coating of high-end wooden furniture to enhance the adhesion between the coating and the wood, and improve the wear resistance, scratch resistance and aesthetics of the furniture.

[0121] New energy battery packaging: The packaging material used for battery shells provides effective protection for batteries with its good adhesion and thermal stability, improving the safety and service life of batteries.

[0122] Example 2 may perform better in some aspects. The reasons are as follows:

[0123] The amount of raw materials used is relatively balanced, and the ratio of phenol to formaldehyde solution is moderate, which is conducive to controlling costs and fully proceeding with the reaction.

[0124] The raw materials used, such as potassium hydroxide catalyst and titanate coupling agent, are relatively common in the market and are easy to obtain.

[0125] The settings of reaction temperature and time are relatively reasonable, which can ensure that the reaction proceeds fully without excessively increasing production time and energy consumption.

[0126] The embodiments of the present invention are given for the purpose of illustration and description, and are not intended to be exhaustive or to limit the invention to the disclosed forms. Many modifications and variations will be apparent to those of ordinary skill in the art. The embodiments are selected and described in order to better illustrate the principles and practical applications of the present invention and to enable those of ordinary skill in the art to understand the present invention and thereby design various embodiments with various modifications suitable for specific uses.

Claims

1. A preparation process of a high-adhesion phenolic resin, characterized in that: The following steps are involved: The process includes preparing raw materials, pre-treating a reaction vessel, initially mixing, adjusting pH value, heating reaction, intermediate monitoring, introducing additives, terminating reaction, and drying. 80-150 g of phenol and 120-220 g of a 37% formaldehyde solution are added to a pre-treated, clean and dried reaction vessel, and stirred evenly. The stirring speed is controlled to be 100-300 rpm, and the stirring time is 20-40 minutes, so that the phenol and formaldehyde solutions are fully mixed.

2. A process for preparing a high-adhesion phenolic resin as claimed in claim 1, characterized in that: 3-10 grams of sodium hydroxide, potassium hydroxide, sodium carbonate, ammonia water or ammonium chloride are used as a catalyst to adjust the pH value of the reaction system to the range of 9.0-10.

5.

3. A process for preparing a high-adhesion phenolic resin as claimed in claim 1, characterized in that: During the reaction process of heating to 80-100°C, which lasts for 1-3 hours, the reaction degree is regularly monitored by a rotational viscometer, spectrophotometry, etc., with a monitoring interval of 20-40 minutes.

4. A process for preparing a high-adhesion phenolic resin as claimed in claim 1, characterized in that: During the 1-2.5 hour period of the reaction, add 8-15 grams of silane coupling agent (KH-550, KH-792, KH-560), titanate coupling agent (NDZ-101), maleic anhydride grafted material and other adhesion enhancing additives, and continue stirring for 20-40 minutes.

5. A process for preparing a high-adhesion phenolic resin as claimed in claim 1, characterized in that: When the viscosity reaches a predetermined value and the residual formaldehyde content is less than 1%, or infrared spectroscopy analysis shows that the functional group conversion reaches the expected level, or the thermal stability test meets the requirements, the reaction is terminated by natural cooling, adding a terminator, rapidly cooling, or passing cold air.

6. A process for preparing a high-adhesion phenolic resin as claimed in claim 1, characterized in that: The reaction product was filtered and washed 2-3 times with deionized water, ethanol, acetone, distilled water or toluene to remove impurities.

7. A process for preparing a high-adhesion phenolic resin as claimed in claim 1, characterized in that: The treated product is dried in a vacuum oven at a temperature of 60-85° C. for 3-6 hours to obtain a high-adhesion phenolic resin.

8. A process for preparing a high-adhesion phenolic resin as claimed in claim 7, characterized in that: The reaction temperature is controlled within the range of 80° C. to 100° C., the reaction time is 1 hour to 3 hours, the order and speed of adding each raw material follow specific specifications, the amount of phenol is 80 g to 150 g, the amount of 37% formaldehyde solution is 120 g to 220 g, the amount of catalyst is 3 g to 10 g, and the amount of additives is 8 g to 15 g.

9. A process for preparing a high-adhesion phenolic resin as claimed in claim 8, characterized in that: When high-adhesion phenolic resin is used in industrial production, it is necessary to be equipped with reaction equipment and monitoring systems to ensure precise control of process parameters and safe and stable production processes. The pH value of the reaction system is controlled between 9.0 and 10.

5.

10. A process for preparing a high-adhesion phenolic resin as claimed in claim 8, characterized in that: The purity of raw materials must be no less than 98%, the cleanliness of the production environment must reach Class 100,000, and the operational error of each step must be controlled within ±5%.